INCENTIVE STRUCTURE AND ITS EFFECT ON REFERRALS: AN ANALYSIS OF THE ROLE OF SELF-CONSTRUCTION AS A DETERMINANT - Aripin, Zaenal; Haryaman, Adang; Sikki, Nurhaeni (Yayasan Kreatif Indonesia Emas, 2024)
The experience of referring others in a referral incentive program has a significant impact on an individual's self-perception and their propensity to engage in future referral activities. This study investigates how referral experiences influence individuals' self-perceptions and their motivation to engage in referral activities, as well as factors that moderate the relationship between referral experiences, incentive structures, and participation behavior. Using a qualitative approach, we analyzed data from in-depth interviews with referral program participants as well as participant observation in the program environment. Our findings suggest that individuals' self-construal plays a key role in moderating the relationship between incentive structure and their decisions to participate in referral programs. Individuals with strong self-construals tend to respond better to incentives provided, while individuals with low self-construals may experience negative impacts such as decreased motivation or anxiety regarding their performance. However, a successful referral experience can also strengthen an individual's identity as an effective influence or recommender, thereby increasing their motivation to continue participating in the referral program in the future. The practical implication of these findings is the importance of companies paying attention to psychological and social factors that influence individual self-perceptions in designing effective incentive strategies in encouraging participation in referral programs. By strengthening social support, increasing transparency and fairness, and understanding individual needs and preferences, companies can create a supportive environment for individuals to refer others with confidence and integrity.